Ocena atrakcyjności inwestycji w akcje spółek społecznie odpowiedzialnych na podstawie indeksu RECPECT - Gołaszewska-Kaczan, Urszula; Kilon, Jarosław; Marcinkiewicz, Jacek (Annales. Etyka w Życiu Gospodarczym, 2016)
In both theory and practice, it is emphasised that engaging in CSR actions bringsmany benefits to companies. One of the commonly listed advantages is more trustfrom investors, which enables the achievement of superior returns from securitiesissued by socially responsible firms. The paper endeavours to investigate whetherthis benefit can be also noticed among businesses in the Polish index of sociallyresponsible companies RESPECT. The study involves firms included in the RESPECTindex from its inception (November 2011) to the end of 2015. The authorscompared the RESPECT index with selected Polish market indices between 2009and 2015. Empirical studies, based on an analysis of returns, risk, dividend yieldsand shareholder structure, facilitated the assessment of the attractiveness of investmentsin the shares of socially responsible businesses against the background ofother firms quoted on the Warsaw Stock Exchange.